2020
DOI: 10.3389/fonc.2020.00906
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Circular RNA hsa_circRPPH1_015 Exerts an Oncogenic Role in Breast Cancer by Impairing miRNA-326-Mediated ELK1 Inhibition

Abstract: Background: Breast cancer (BC) represents a heterogeneous disease with distinct subtypes and high tumor metastatic potentials. Recent researchers identify the implication of circular RNAs (circRNAs) in the initiation of BC. Herein, we uncover a novel circRNA hsa_circRPPH1_015 as a tumor promoter in BC. Methods: A total of 86 paired cancerous and non-cancerous tissues were surgically resected and collected from BC patients. Cell proliferation, colony formation, and cell invasion were examined by Edu staining, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…We demonstrated that ELK1 is upregulated in LSCC and acts as a target gene of miR-340-3p as well as a ceRNA of circPPFIA1. ELK1 has been reported to be targeted by miR-30-5p, miR-185-5p, and miR-326 [32][33][34], but this is the first study wherein ELK1 was proven to be a target of miR-340-3p. However, we did not determine the downstream genes activated by ELK1.…”
Section: Discussionmentioning
confidence: 88%
“…We demonstrated that ELK1 is upregulated in LSCC and acts as a target gene of miR-340-3p as well as a ceRNA of circPPFIA1. ELK1 has been reported to be targeted by miR-30-5p, miR-185-5p, and miR-326 [32][33][34], but this is the first study wherein ELK1 was proven to be a target of miR-340-3p. However, we did not determine the downstream genes activated by ELK1.…”
Section: Discussionmentioning
confidence: 88%
“…Previous literature has manifested that circRNAs are also correlated with CSC progression; however, the roles of circRPPH1 in GC progression has never been revealed before. Currently, we found that progression, [17][18][19][31][32][33] among which, YAP1, miR-296-5p, and HMGA2…”
Section: Circrpph1 Acts As An Mir-375 Sponge In Gc Cellsmentioning
confidence: 99%
“…16 As a result, the relationship between circRNAs and miR-375 in GC stemness attracted our interests. Recently, circRPPH1 was firstly identified in breast cancer 17 and found to hold oncogenic roles in breast cancer progression. 18 Furthermore, it was found that circRPPH1 could promote the cell proliferation, migration and invasion of non-small cell lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that cancer stem cells (CSCs) are the initiator cells of cancers and are responsible for cancer treatment failure owing to their pluripotency and self-renewal characteristics, leading to tumor recurrence [102,103]. Other circRNAs also mediate breast cancer cell development and progression, including hsa_circ_001783, hsa_circRNA _002178, hsa_circRPPH1_015, circ_0007255, circ-TFF1, hsa_circ_0000515, and hsa_circ_0068033, via sponging miR-200c-3p, miR-328-3p, miR-326, miR-335-5p, miR-326, miR-296-5p, and miR-659, respectively [104][105][106][107][108][109][110].…”
Section: Circrnas and Tumor Development And Proliferationmentioning
confidence: 99%